1980
DOI: 10.1073/pnas.77.3.1602
|View full text |Cite
|
Sign up to set email alerts
|

Clonal anergy: Persistence in tolerant mice of antigen-binding B lymphocytes incapable of responding to antigen or mitogen

Abstract: The purpose of these experiments was to determine the degree of reduction in the number of antigenbinding B lymphocytes in the spleens of mice that had been rendered tolerant in the perinatal period. Newborn or pregnant mice were injected with fluorescein (Flu) coupled onto human gamma globulin, and the spleen cells of the neonatally injected mice, or of the offspring of the pregnant mice, were analyzed 1-6 weeks later. Tolerogen doses were chosen so as to achieve either a two-thirds reduction (low dose) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
124
0
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 219 publications
(126 citation statements)
references
References 24 publications
1
124
0
1
Order By: Relevance
“…Anergy is thought to arise as the immature B cells leave the bone marrow and enter the periphery (12,42,43). If they meet Ags without the appropriate T cell help (CD40 Ligand), they are anergized or deleted.…”
Section: Discussionmentioning
confidence: 99%
“…Anergy is thought to arise as the immature B cells leave the bone marrow and enter the periphery (12,42,43). If they meet Ags without the appropriate T cell help (CD40 Ligand), they are anergized or deleted.…”
Section: Discussionmentioning
confidence: 99%
“…These notions, originally proposed by Nossal and Pike [3,4], were apparently supported by in vivo studies in the HEL/anti-HEL transgenic model, where high avidity BCR interactions led to the elimination of HEL-reactive cells in the bone marrow, while low avidity interactions indeed yielded self-reactive cells in the periphery [5]. However, following description of the TR compartment, Fulcher and Basten demonstrated that these 'anergic' B cells achieved entrance to the TR pools, but nonetheless died rapidly before entering mature pools [6].…”
Section: B Cells Undergo Both Negative and Positive Selection As Theymentioning
confidence: 99%
“…Co-stimulatory signals implicated in the activation of the TcR include tyrosine kinases, interleukins, the B7 family (Chen et al, 1993) (Nossal and Pike, 1980;Goodnow et al, 1991). The concept of a population of down-regulated T-and B-cell repertoires with a threshold affinity for silencing was advanced by Nossal (1983) as one of 'immune ignorance'.…”
Section: Mechanisms Of Tumour Escape From Immunological Recognitionmentioning
confidence: 99%